Liquid range of ionic liquid – Metal salt mixtures for electrochemical applications. (July 2019) - Salgado, J.; Parajó, J.J.; Villanueva, M.; Rodríguez, J.R.; Cabeza, O.; Varela, L.M.
Highlights: The effect of 4 nitrate salt addition on liquid range of EAN was analysed. Salt addition induces decreases on melting temperature. Salt addition has not effect on boiling point. Pseudolattice metal-anion complexes are formed in polar nanoregions of the IL. Abstract: The effect of the nitrate salt addition on the liquid range of the protic ionic liquid ethylammonium nitrate (EAN) was studied in this work. The salts used were monovalent, LiNO3 ; divalent, Mg(NO3 )2 and Ca(NO3 )2, and trivalent, Al(NO3 )3 ; inorganic salts containing metals relevant for electrochemical applications. Solid-liquid transitions, which define the lower limit of the liquid range of the fluids, were determined using differential scanning calorimetry (DSC), whereas the upper limit, which is given by degradation or boiling temperatures, was determined by means of thermogravimetric analysis (TGA). Our results show that salt addition induces melting-point depressions, but no significant boiling point elevations were detected. The so-called nanostructured solvation mechanism is used in order to rationalize the thermodynamics of the mixtures in terms of the occurrence of highly incompressible, low mobility solvation complexes [M(NO3 )n ] z + −n in the polar cavities of the IL giving rise to pseudo-lattice nanocrystals that are stable in the liquid phase.